Aplicação de nitrogênio no crambe cultivado após culturas de cobertura - Tomassoni, Fabíola (2015)
Nitrogen is one of the great impact of elements in crop productivity, but little is known about its effect on crambe nutrition as a function of crop ground cover predecessors to the no-till system. The study aimed to evaluate the dry matter accumulation of cover crops and the effect of nitrogen application coverage in the subsequent crop crambe. The experiment was conducted in Santa Helena, State of Parana in a Rhodic Hapludox (Red Latosol in the Brazilian classification). The experimental design was a randomized block in a split plot design with four replications. The plots were Pennisetum glaucum, sudanense Sorghum, Sorghum bicolor and Crotalaria juncea, and the subplots of absence or presence of nitrogen in coverage (0 and 70 kg ha-1). Cover crops showed similar results (p ≤ 0.05), dry matter, whose accumulations were 11,551, 11,313, 10,692 and 10,268 kg ha-1 for sorghum, sudan grass, sun hemp and millet, respectively. The crambe culture was influenced by the interaction between the factors cover crops  nitrogen fertilization, the nitrogen fertilization did not influence the relative chlorophyll index and the total N content when the crambe was grown on straw of sunn hemp. The isolation of cover crops positively affected the dry matter accumulation, the number of plants and productivity of crambe grains, especially the sun hemp. Except the thousand grain weight, the other crambe yield components were positively influenced by nitrogen fertilization. The nitrogen fertilization provided higher productivity crambe (1,347 kg ha-1).